2017
DOI: 10.1093/annonc/mdw538
|View full text |Cite
|
Sign up to set email alerts
|

Do Contemporary Randomized Controlled Trials Meet ESMO Thresholds for Meaningful Clinical Benefit?

Abstract: Less than one-third of contemporary RCTs with statistically significant results meet ESMO thresholds for meaningful clinical benefit, and this represents only 15% of all published trials. Investigators, funding agencies, regulatory agencies, and industry should adopt more stringent thresholds for meaningful benefit in the design of future RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 15 publications
1
45
1
1
Order By: Relevance
“…About a third of “positive” randomised controlled trials of cancer drugs report treatment effects that are considered to be clinically meaningful according to the European Society of Medical Oncology Magnitude of Clinical Benefit Scale 514. Moreover, there is no association between magnitude of benefit and drug price 15.…”
Section: Introductionmentioning
confidence: 99%
“…About a third of “positive” randomised controlled trials of cancer drugs report treatment effects that are considered to be clinically meaningful according to the European Society of Medical Oncology Magnitude of Clinical Benefit Scale 514. Moreover, there is no association between magnitude of benefit and drug price 15.…”
Section: Introductionmentioning
confidence: 99%
“…14 Studies analyzing clinical benefit of FDA-approved drugs using these frameworks have concluded that most drugs did not have meaningful clinical benefit. [33][34][35] Although these frameworks can be used to quantify benefits, clinicians would require an in-depth and detailed understanding of the intricacies of the framework algorithms to understand the possibilities that lead to a specific score (ASCO-VF) or grade (ESMO-MCBS), which may make the output less accessible to clinicians or decision-makers with respect to the underlying magnitude of survival benefit of oncology drugs. RMST is an easily interpretable way to describe the magnitude of benefit because it is measured in the natural unit of time (eg, months), which makes interpretation of the magnitude directly accessible to clinicians and decisionmakers.…”
Section: Discussionmentioning
confidence: 99%
“…-American Society of Clinical Oncology, ASCO) [26], а среди препаратов, изучавшихся в 226 рандомизированных контролируемых исследованиях (РКИ), клинически значимая польза в соответствии с критериями Европейского общества медицинской онкологии (англ. -European Society of Medical Oncology, ESMO) наблюдалась лишь в 70 (31%) исследованиях [27]. Причем в реальной медицинской практике польза от применения этих препаратов, согласно результатам ряда исследований, может быть значительно меньше, чем в РКИ, в связи с более пожилым возрастом больных и наличия у них большего числа коморбидностей по сравнению с тщательно отобранными участниками клинических исследований [28][29][30][31].…”
Section: соотношение стоимости и терапевтической пользы инновационныхunclassified